Pineapple Mushroom Medium UMP research output launched - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
SERDANG, 8 August 2022 - The Malaysian Pineapple Industry Board (LPNM) recently launched an innovation based on pineapple waste produced in collaboration with UMP research led by Associate Professor Dr. Aizi Nor Mazila Ramli in conjunction with the Malaysian Agriculture, Horticulture and Agrotourism Exhibition (MAHA) from 4 to 14 August 2022.